The Relationship between the HPV Cervical Infection and Intraepithelial Colorectal Lesions in Women - Olga S. Alyautdina (Journal of Global Pharma Technology, 2018)
A histological structure of anal epithelium shows obvious parallels with the structure of cervical epithelium including the presence of a transformed zone at the border between two types of epithelial cells.  In this connection, a process of anal benign tumor pathogenesis is similar to cervical cancer. In the present work, with the use of liquid cytology, a comparison of colorectal HPV infection in women patients with cervix dysplasia and control group of patients with no cervix pathology has been performed. The cytological investigation was performed with the use of a method of liquid cytology BD ShurePath based on a system of automatized scanning of preparations BD Focal Point. Identification of high oncogenic risk HPV was made with the use of a hybrid capture method (HPV digene-test hybrid capture II). Using cytological investigation of colon scrapings, we revealed intraepithelial damages of colon epithelium most probably associated with HPV infection in 24% of patients from the high risk group. In the same time, there were no similar changes in the control group of patients. Our results show that HPV-associated cervix pathology is a risk factor for colon intraepithelial HPV-associated damages development.  These patients are in the high risk group for colorectal cancer development and they must experience a regular corresponding medical examination. Keywords: HPV infection, Cervical cancer, Colorectal cancer, Liquid cytology.